Factors influencing unable to eat healthy and nutritious food among Indonesian onset COVID-19 pandemic - Mamahit, Adi Yeremia; Suryani, Dyah; Suyitno, Suyitno; Akbar, Hairil; Sari, Dewi Puspito; Rahmawati, Ade; Nuraeni, Tating; Supriatin, Supriatin (Intelektual Pustaka Media Utama, 2024)
Nearly every aspect of household life has been touched by the coronavirus disease (COVID-19) pandemic, including the amount and quality of food consumed by the family. This study aimed to examine the factors associated with unable to eat healthy and nutritious food onset of the COVID-19 pandemic in Indonesia. This study used data from Rapid Gender Assessment Survey developed by United Nations Women from September to December 2021. Totally 2,285 respondents aged >18 years old with access to mobile phones have been selected by random digit dialing (RDD). The multivariate analysis revealed living in the town, who graduated from secondary, primary, and no education, households with five or more members, income changes during the pandemic, and those who had not completed vaccine COVID-19 were 1.44; 1.57; 1.73; 2.06; 1.26; 2.74; 1.29 times more likely to be unable to eat healthy and nutritious food. In conclusion, 39.17% of respondents were unable to eat healthy and nutritious food, and factors of changes in income had the biggest impact. Future research could examine the impact of the pandemic on people's capacity to access and buy wholesome food.